A Physics Based Novel Approach for Travelling Tournament Problem: Optics Inspired Optimization - Alatas, B.; Bingol, H. (Kaunas Univ Technology, 2019)
Computational intelligence search and optimization algorithms have been efficiently adopted and used for many types of complex problems. Optics Inspired Optimization (OIO) is one of the most recent physics inspired computational intelligence methods which treats the search space of the problem to be optimized as a wavy mirror in which each peak is assumed to reflect as a convex mirror and each valley to reflect as a concave one. Each candidate solution is treated as an artificial light point that its glittered ray is reflected back by the search space of the problem and the artificial image is formed based on mirror equations adopted from Optics, as a new candidate solution. In this study, OIO for the first time has been designed as a solution search strategy for travelling tournament problem which is one of the current sport problems and aids to minimize transportation and total movement of teams. Furthermore, this problem has been firstly solved by League Championship Algorithm and obtained results from both synthetic and real datasets have been compared. By this study, new application areas for OIO and LCA have been introduced. Obtained results show the superiority of OIO which is a novel algorithm and seems to efficiently solve many complex problems.
Keywords: Computational intelligence optimization; optics inspired optimization; travelling tournament problem; artificial intelligence